2023
DOI: 10.1530/joe-23-0079
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic neuroendocrine integration of reproduction and metabolism in mammals

Abstract: Reproduction in mammals is an extremely energy-intensive process and is therefore tightly controlled by the body's energy status. Changes in the nutritional status of the body cause fluctuations in the levels of peripheral metabolic hormone signals, such as leptin, insulin, and ghrelin, which provide feedback to the hypothalamus and integrate to coordinate metabolism and fertility. Therefore, to link energy and reproduction, energetic information must be centrally transmitted to Gonadotropin-releasing hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 165 publications
0
1
0
Order By: Relevance
“…It is known that the PMV neurons express the leptin receptor (Elmquist et al 1998). Moreover, a recent publication showed that PACAP-glutamatergic neurons that respond to leptin, located in the PMV can regulate the release of GnRH by innervating a subset of Kisspeptin neurons in the Arc and in the RP3V (Yang et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the PMV neurons express the leptin receptor (Elmquist et al 1998). Moreover, a recent publication showed that PACAP-glutamatergic neurons that respond to leptin, located in the PMV can regulate the release of GnRH by innervating a subset of Kisspeptin neurons in the Arc and in the RP3V (Yang et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Besides the reproduction-linked behavioral functions of the Kp system extensively reported in the literature, another topic widely discussed is kisspeptin's role in energy balance control (Navarro 2020, Yang, Zhao et al 2023. A series of studies showed that female Kiss1r KO mice displayed decreased metabolism and obesity despite decreased feeding (Tolson, Garcia et al 2014, Tolson, Garcia et al 2016, Tolson, Marooki et al 2019) and that kisspeptin can modulate the activity of hypothalamic hunger/satiety circuits (Fu andvan den Pol 2010, Nestor, Qiu et al 2016).…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Clinical algorithms for kisspeptin treatment in ovulation disorders are constantly being developed due to the beneficial effect of this neuropeptide on follicle maturation, as assessed by maturity-related gene expression [327]. Therefore, the variability of the functional balance within the PRLkisspeptin interaction may determine the dominant influence of GnRH or PRL on a given stage of the sexual cycle, including ovulation [13,[328][329][330].…”
Section: Prl-kisspeptin Interactionmentioning
confidence: 99%